Modal Analysis of the Scraper Conveyer Sprocket Assembly based on the ANSYS - Yu Pengfei; Zeng Qingliang; Hu Yanqing (Jixie chuandong)
In order to obtain the natural frequency and vibration mode of the chain transmission system of the scraper conveyor,the meshing process of the sprocket and the round link chain is analyzed to obtain the key meshing state during the meshing process. The modal analysis of the different meshing states is carried out by ANSYS software. A general natural frequency change law in a complete meshing process is obtained,by the method of fitting data points and the natural frequency range of the chain transmission system is obtained.Which effectively solve the problem that single sprocket static mode analysis cannot meet practical condition.The solving results provide the basis for the dynamics research and optimization design of the chain transmission system of the scraper conveyor.